Idiopathic granulomatous mastitis: a diagnostic challenge - Pandey, Divya; Syed, Anjum; Ravi, Bina; Chowdhury, Nilotpal; Kapoor, Aakriti; Mehrotra, Surabhi; Gupta, Priyanka; Pranoy, Pranoy (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Idiopathic granulomatous mastitis is an uncommon and benign inflammatory breast disease that usually occurs in young women of childbearing age. Most common presentation is a slowly growing breast mass that is hard in consistency and can greatly mimic breast cancer. Mammographic and ultra-sonographic findings are non- specific and usually mimic malignant masses leading to higher BIRADS grading in reports. The only way to reach a definitive diagnosis is by histopathological diagnosis. Material & Methods: In the present study eight patients were presented to The Integrated Breast Care Centre (IBCC) department of AIIMS Rishikesh with breast lump or nipple discharge during January 2019 to June 2019. All the patients underwent mammography and ultrasonography followed by FNAC or Biopsy of the lesion as findings were mimicking malignant etiology. Results: On HPE all the patients showed features of granulomatous inflammation and diagnosis of idiopathic granulomatous mastitis was made. TB was excluded by CBNATT (Cartridge Based Nucleic Acid Amplification Test) examination of the aspiration cytology samples. To our knowledge, such a report is the first of its kind to address this topic in this region. Conclusion: In a young child-bearing age group female presenting with breast mass a differential of idiopathic granulomatous mastitis should also be considered. The clinicians as well as radiologists should be aware of this entity so that appropriate management may be done.